2016
DOI: 10.3945/ajcn.115.111336
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-based nutrient supplements for pregnant women reduce newborn stunting in a cluster-randomized controlled effectiveness trial in Bangladesh

Abstract: Prenatal lipid-based nutrient supplements can improve birth outcomes in Bangladeshi women, especially those at higher risk of fetal growth restriction. This trial was registered at clinicaltrials.gov as NCT01715038.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
261
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(276 citation statements)
references
References 30 publications
4
261
1
2
Order By: Relevance
“…The overall hypothesis of the study was that the provision of LNS-PL to women and/or LNS-C to their offspring would result in larger positive changes in maternal and child nutrition outcomes than would the provision of iron and folic acid (IFA) to women and MNP or no supplementation for their children. We previously reported that LNS-PL reduced stunting and small head size at birth in the RDNS sample (12). This report describes the effects of the RDNS intervention on child development (secondary) outcomes during the first 24 mo.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…The overall hypothesis of the study was that the provision of LNS-PL to women and/or LNS-C to their offspring would result in larger positive changes in maternal and child nutrition outcomes than would the provision of iron and folic acid (IFA) to women and MNP or no supplementation for their children. We previously reported that LNS-PL reduced stunting and small head size at birth in the RDNS sample (12). This report describes the effects of the RDNS intervention on child development (secondary) outcomes during the first 24 mo.…”
Section: Introductionmentioning
confidence: 84%
“…Other regular services provided by CHDP included maternity services at a safe delivery unit (SDU) in each union; home visits for antenatal, postnatal, and primary child care by community health workers (CHWs) and village health volunteers; and educational group sessions to promote maternal and child health. A further description of the study setting is reported elsewhere (12).…”
Section: Study Setting and Designmentioning
confidence: 99%
See 3 more Smart Citations